Internal and external determinants of non-performing loans in Malayan Banking Berhad / Mohamad Azrul Azraf Mohamad Noor - Mohamad Noor, Mohamad Azrul Azraf (Faculty of Business Management, 2018)
The main purpose of this paper is to determine the internal and external factors of nonperforming loans in Malayan Banking Berhad over the period from 1997 to 2016. This study would like to determine how the internal factors, return on assets (ROA) and net profit margin (NPM) and external factors, gross domestic product growth (GDP), inflation rate (INF) and unemployment rate (UNEMP) influence the level of nonperforming loans in Malayan Banking Berhad specifically. To obtain the results, regression analysis was applied with NPL to stated independent variables. Empirical results of regression shows that only unemployment rate is statistically significant with the NPL while the other factors, return on assets, net profit margin, gross domestic product growth and inflation are statistically insignificant which are contrary to the study expectation. Even though, most of the predictor variables' regression result are insignificant, those results are normal as the findings from the previous researchers conclude the same result as stated. The findings of the previous researchers are referred as the guidelines in determining the type of independent variables to be included. Then, some comparisons between the current regression result and previous findings are done in order to ensure that those results are significant and accurate.